GLAMOR IN THE CONTEXT OF CLASSICAL AESTHETIC CATEGORIES AND PARACATEGORIES OF NONCLASSICAL AESTHETICS - Безугла, Р. І. (Art and Design, 2019)
The purpose of the article is to reveal the essential specificity of glamor as an ambivalent artistic phenomenon in relation to classical aesthetic categories and para-categories of non-classical aesthetics. Theoretical and methodological basis for the study were such general scientific approaches as: systemic, the use of which allowed to explore glamor as an ambivalent, multidimensional artistic phenomenon; axiological - contributed to the definition of the role and importance of glamor values in cultural and artistic transformation processes; structural-functional approach allowed to analyze the stylistic laws and principles of the formation of a glamorous ideal in the context of modern art. Results. The results of the study have a theoretical significance, which consists in expanding the subject field of art history, in particular, glamor is considered as a category of non-classical aesthetics, as a kind of temporary simulacrum of a category that may eventually be included in the categorical apparatus of the 21st century. Scientific novelty. The analysis of glamor, as an ambivalent artistic and creative phenomenon, which aims to unify the aesthetic ideal and symbolic values. The place of glamor in the “ruler” of classical aesthetic categories and values of postmodernism has been determined, the correlation of glamor with the artistic and aesthetic essence of art has been revealed. Practical significance. The results contribute to a deeper understanding of glamor as an artistic phenomenon, including further study of the essential specifics of glamor from different aspects and in the context of the relationship between the categories «beauty» and «glamor».